Demographic Pattern Of Unhealthy Application Of Cosmetics By Female Salon Operators In Tertiary Institutions In Rivers State - I. L, Onyekwere; J. O, Onyezere, (Riviera Publishing, 2023)
This study investigated demographic pattern of harmful cosmetic application among female salon workers in tertiary institutions in Rivers State. Using a detailed descriptive cross-sectional design, the study surveyed 1200 salon operators across ten institutions with a rigorously validated questionnaire. The main goal was to understand the complex relationship between demographic factors such as age, experience, and education level, and the prevalence of unhealthy cosmetic practices. Through careful analysis of both descriptive and inferential statistics, the study found that unhealthy cosmetic practices were alarmingly common among salon operators. Dibutylphthalate was identified as the most frequently used toxic chemical. The study further revealed that younger operators aged 16-19, those with 4-7 years of experience, and those without formal education were more likely to engage in these harmful practices. These findings highlight the potential health risks associated with the use of unregulated cosmetics, especially among younger, less-educated operators. The study emphasizes the urgent need for education and awareness about the potential hazards of certain chemicals in cosmetics. In response to these findings, the study concludes with a strong recommendation for university authorities to take proactive steps to educate salon operators about these risks. It stresses the importance of adhering to safe cosmetic practices. By doing so, we can promote a safer and healthier salon industry for both operators and customers.